Evaluation of The Effect of Outer Skin Slope on Fire Safety in Double-Skin Façade Systems - Figen Beyhan; Mehmet Akif Yıldız (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2024)
In order to increase energy efficiency and user comfort, double skin façade designs are becoming increasingly popular in the built environment as an alternative to traditional façede and curtain walling systems. The vertical cavity between the outer and inner skins of double skin façade systems, which is critical for natural ventilation, can destroy the effectiveness of façade designs by creating fire hazards due to the creation of uninterrupted areas between spaces. It is essential for the sustainability of the buildings to make appropriate fire safety designs for the risks of spreading toxic gases released in a possible fire through the double skin façede cavity to monitor the design before the building is built and to take the necessary precautions. Therefore, that paper developed a numerical model using computational fluid dynamics to monitor the smoke propagation through the cavity of the double skin façade and the temperature changes in the building. As a contribution to the physical modeling studies of double skin façade systems in the literature, the effect of changing the slope of the outer skin on smoke propagation and temperature changes was investigated. A design model was created by developing 9 scenarios: 4 wide angles, 4 acute angles, and a right angle, each with an angle varying by 3 degrees. While acute-angle cavity designs increased the flue effect in the cavity and increased the direction speed and density of the smoke towards the cavity, wide-angle cavity designs reduced the ambient temperature.